2019
DOI: 10.1007/s10961-019-09754-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on accelerators

Abstract: Over the past 15 years, accelerators emerged as a popular and distinct new form of intermediary organization, playing a key role in supporting entrepreneurial and innovation activities. To date, despite significant growth in accelerators research, there is still little understanding of how different forms of accelerators operate, and what outcomes they produce across different contexts. This paper reviews the existing scholarly research on accelerators using the Context-Intervention-Mechanism-Outcome framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 85 publications
0
97
0
13
Order By: Relevance
“…In the context of this study, CIMO refers to how university-industry collaborations are carried out, considering the context in which they occur, as well as interventions, mechanisms, and results in terms of socioeconomic impacts. We extracted the following information: authors, year of publication, title, journal, nature of the study (conceptual or empirical), methodology [15][16][17], and the country of origin of the author's institution [16,17]. We used the context-intervention-mechanismsoutcome (CIMO) methodology to conduct our analysis [14].…”
Section: Conducting (Stage 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of this study, CIMO refers to how university-industry collaborations are carried out, considering the context in which they occur, as well as interventions, mechanisms, and results in terms of socioeconomic impacts. We extracted the following information: authors, year of publication, title, journal, nature of the study (conceptual or empirical), methodology [15][16][17], and the country of origin of the author's institution [16,17]. We used the context-intervention-mechanismsoutcome (CIMO) methodology to conduct our analysis [14].…”
Section: Conducting (Stage 2)mentioning
confidence: 99%
“…In the CIMO perspective, the contexts analyzed are the internal and external environments that influence behavioral change [14,16]. This systematic literature review identified both external and internal contexts: (1) the external contexts were the socioeconomic conditions and the national and regional laws and policies; (2) the internal contexts were the universities' characteristics, the firms' characteristics, and the researchers' characteristics.…”
Section: Contextmentioning
confidence: 99%
“…Thus, organizations are driven to find suitable forms and structures to minimize these characteristics that are so disparate between large corporations and startups, bringing them together to develop capabilities that result in innovation. Corporate accelerators are an effective model for this, as they are characterized by mechanisms that support the validation of ideas and products, that provide learning models, and that support growth and market entry for companies that are starting their activities in the same way that the accelerators support innovation (Crișan et al, 2019).…”
Section: Interorganizational Relationshipsmentioning
confidence: 99%
“…Among the various mechanisms that explain the role of corporate accelerators, we highlight the provision of support to increase access and growth of startups in the market (Crișan, Salanță, Beleiu, Bordean, & Bunduchi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Uma forma usual e crescente de aproximar startups e grandes empresas é por meio dos programas de aceleração liderados por corporações consolidadas, os quais, desde o início de 2010, aumentaram em todo o mundo (Moschner et al, 2019;Shankar & Shepherd, 2019;Urbaniec & Żur, 2020). Estudos empíricos mostram que as aceleradoras corporativas possibilitam, dentre outros, a prestação de suporte para aumentar o acesso e o crescimento das startups no mercado (Crișan et al, 2019), bem como o desenvolvimento de capacidades em startups, destacando a capacidade de absorção de conhecimento (Cajuela & Galina, 2020).…”
Section: Introductionunclassified